148k views
5 votes
Solve for x in this equation: a - bx = cx + d

2 Answers

2 votes

Answer:

1. cx

2. a

3. x

4. (-b -c)

Explanation:

1. Subtract cx - from both sides

2. Subtract a from both sides

3. Factor x

4. Isolate x by dividing both sides of the equation by (-b -c)

Solve for x in this equation: a - bx = cx + d-example-1
User CDuv
by
5.6k points
4 votes

Answer:

a - d / b + c = x

Explanation:

a - bx = cx + d

a = bx + cx + d

a - d = bx + cx

a - d = x ( b + c )

a - d / b + c = x

User Irish Buffer
by
4.9k points